The Correlation of Sponsorship Attractiveness and Achilles Television Advertising Exposure with Brand Image of Achilles - Muhammad Faizuddin; Dra. Sri Widowati Herieningsih, MS (Interaksi Online, 2017)
Competition in the automotive industry in Indonesia is getting tight. Various attempts were made by the company to be able to compete and win the competition. Marketing has a very important role in a tight competition between companies. No exception Achilles doing one marketing strategy that is in partnership with an official sponsor of Manchester United are aiming to increasing its brand image. In partnership, Achilles held several events sponsorship and advertising relating to that partnership. The purpose of this study was to determine the relationship between sponsorship attraction and Achilles advertising exposure on television with Achilles brand image. This study uses the Integration of Information Theory and Cognitive Response Theory. Samples technique using Non-Probability Sampling with purposive sampling. Respondents in this study is a fan of Manchester United, who have a car and they are exposed information of Achilles sponsorship program to Manchester United as well as Achilles television advertising in Semarang. To test the hypothesis, this study used Kendall correlation test. Results from the study showed that the attractiveness of sponsorship with the Achilles brand image does not have a relationship, where the significance value is 0,363. Furthermore, for Achilles television advertising exposure was also not associated with the brand image of Achilles, where the significance value is 0.244. Thus, these results do not accordance with the initial hypothesis which states that there is a relationship between the sponsorship attraction and Achilles advertising exposure on television with Achilles brand image. The advice given from this research for the company is to change the marketing strategy by a partnership with who have close relation with the Achilles product and create an ad that is packaged more attractively such as using use the Manchester United player who more famous as commercials and not only made in one version by using the right medium, so that marketing activities can provide benefits to the maximum for the company.